HIV gp120 upregulates tonic inhibition through α5-containing GABAARs. (1st May 2019) - Green, Matthew V.; Thayer, Stanley A.
Abstract: HIV-Associated Neurocognitive disorder (HAND) affects nearly half of infected patients. The HIV envelope protein gp120 is shed by infected cells and is a potent neurotoxin in vitro that reproduces many aspects of HAND when expressed in vivo . Here, we show that HIV gp120 increases the amplitude of a tonic current mediated by γ-aminobutyric acid type-A receptors (GABAA Rs). Treating rat hippocampal cultures with 600 pM gp120IIIB for 4 h increased a tonic bicuculline-sensitive current, which remained elevated for 24 h. The increased current resulted from upregulation of extrasynaptic α5-containing GABAA Rs, as indicated by inhibition with the selective inverse agonist basmisanil. Treatment with gp120 increased α5-GABAA R immunoreactivity on the cell surface without new protein synthesis. The increase in tonic inhibition was prevented by a C-X-C chemokine receptor type 4 (CXCR4) antagonist or elimination of microglia from the culture. Treatment with interleukin-1β (IL-1β) increased the tonic current and an IL-1 receptor antagonist blocked the gp120-evoked response. Pharmacological or genetic inhibition of p38 mitogen-activated protein kinase (MAPK) prevented the gp120-evoked increase in tonic current and direct activation of a mutant form of p38 MAPK expressed in neurons increased the current. Collectively, these data show that gp120 activates CXCR4 to stimulate microglia to release IL-1β. Subsequent stimulation of IL-1 receptors activates p38 MAPK in neurons leading to the upregulation of α5-containing GABAA Rs. Increased tonic inhibition impairs neuroplasticity and inhibition of α5-containing GABAA Rs improves cognitive function in disease models. Thus, gp120-induced upregulation of α5-containing GABAA Rs presents a novel therapeutic target for HAND. Graphical abstract: Image 1 Highlights: HIV envelope protein gp120 increases tonic inhibition through extrasynaptic GABAA Rs. α5-containing GABAA Rs on the cell surface are selectively upregulated by gp120. Increased tonic inhibition occurs via gp120-evoked release of IL-1β from microglia. Stimulation of IL-1 receptors activates p38 in neurons to increase tonic inhibition.